Negligence versus Strict Liability Regimes in Auditing: An Experimental Investigation - Dopuch, Nicholas; King, Ronald R. (The Accounting Review, 1992)
[In this study we assess how different regimes of auditor liability affect the demand for and supply of auditing services. The assessment was made with 15 experimental markets, each of which involved two sellers of assets, two auditors (verifiers), and four buyers. The experimental markets paradigm allowed us to compare the negligence liability regime (six markets) that auditors currently face with two alternatives not currently in existence-a strict liability regime (six markets) and a no-liability regime (three markets). We focused on the extent to which the experimental results conformed to our predictions of (1) sellers' frequency of hiring verifiers and of selecting a costly investment that improved aggregate welfare, (2) verifiers' service fees and their frequency of testing the truthfulness of the sellers' disclosures, and (3) buyers' reliance on the sellers' disclosures and verifiers' reports when pricing the sellers' assets. The predictions varied across the liability regimes primarily because differences in the degree of the verifiers' liability changed their economic incentives to test the truthfulness of the sellers' disclosures. The results show that the no-liability and negligence markets operated in a manner consistent with the predictions, whereas the strict markets deviated from the predictions on several dimensions. Specifically, verifiers in the strict liability markets were hired less often than predicted because they submitted higher offers for their services than sellers were willing to pay. This in turn led to fewer than predicted costly investments by the sellers. Although our general conclusion recognizes that a legal system is an integral part of the auditing institutional infrastructure, we found no evidence of any systematic benefits from imposing a strict liability rule on the verification service. In fact, the results suggest that the negligence liability markets operated at a level of economic efficiency as high or higher than those in the other two regimes. This suggests that the current tendencies of courts and the auditing profession to expand the scope of auditors' liabilities may not achieve the net benefits expected from such expansions.]